The Architecture of Participation: Does Code Architecture Mitigate Free Riding in the Open Source Development Model? - Baldwin, Carliss Y.; Clark, Kim B. (Management Science, 2006)
This paper argues that the architecture of a codebase is a critical factor that lies at the heart of the open source development process. We define two observable properties of an architecture: (1) modularity and (2) option value. Developers can often make informed judgments about modularity and option value from early, partially implemented code releases. We show that codebases that are more modular or have more option value (1) increase developers’ incentives to join and remain involved in an open source development effort and (2) decrease the amount of free riding in equilibrium. These effects occur because modularity and option value create opportunities for the exchange of valuable work among developers, opportunities that do not exist in codebases that are not modular or have no option value.